Creation and Construction: On the Theological Appropriation of Postmodern Theory - Henriksen, Jan-Olav (Modern theology, 2002)
Postmodern theory can be appreciated by theological anthropology along the following lines: it interprets the cultural conditions that shape personal identity, including the elements of construction and contingency in identity-formation. It emphasizes the necessity for a multifaceted approach to the question about what it means to be human, and for avoiding closure. This is expressed in the doctrine of the human as created, as sinner and as restored—as none of these perspectives captures the whole picture. Postmodern theory also focuses on the importance of otherness for establishing identity, thereby offering a new way of interpreting human beings as created in the image of God.